(untitled) (Historia, 2021)
Since the late 1980's the number of students both in Norwegian universities in general as well as at our History Department at the University of Bergen increased substantially. This influx was due to both larger birth cohorts and the government's use of the educational system to camouflage youth unemployment. The trend coincided with an incipient change in pedagogical methods, or at least an understanding of the necessity to change. At many university faculties there was a deep concern that Norwegian undergraduates wrote too few papers. Among history students the main activity was the passive reception of facts and opinions expressed by lectures.